(untitled) (PANGEEA, 2025)
Organization of tourism in regional and local development prospects of the Apuseni Mountains. Apuseni Mountains is a high tourist area but strong potanţial least exploited. Tourism demand far exceeds supply. For the touristic targets in the area have achieved the objectives: diversification and increased quality of tourism services; replenishment action marketing tourism products in the international market and ensure the labour force. This paper presents some specific actions that can lead to achieving these objectives.